When Trauma Survivors Return to Work: Understanding Emotional Recovery - Barski-Carrow, Barbara (Hamilton Books, 2010)
When Trauma Survivors Return To Work explains how managers and co-workers can help foster the process of emotional recovery for employees who have been traumatized and are returning to work. No other source clearly and positively teaches managers and co-workers how to treat fellow workers returning to the workplace after experiencing a rape, a burglary, an armed assault, a violent accident, or witnessing a brutal crime. No one explains what to say to those who have just been told they have a terminal illness, or how to treat an employee whose close family member has committed suicide. It is not helpful for co-workers to deny such traumatic events or remain silent, which is what often happens, or for managers to avoid directly communicating with the traumatized employee. Is there something that managers and co-workers can do to be truly helpful to such sensitively wounded people? The answer is yes. In this illuminating educational approach, Dr. Barski-Carrow shows how managers and co-workers can learn simple ways to make the workplace a better environment for emotional healing.